2010
DOI: 10.2308/accr.2010.85.2.483
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for Cross-Sectional and Time-Series Dependence in Accounting Research

Abstract: We review and evaluate the methods commonly used in the accounting literature to correct for cross-sectional and time-series dependence. While much of the accounting literature studies settings in which variables are cross-sectionally and serially correlated, we find that the extant methods are not robust to both forms of dependence. Contrary to claims in the literature, we find that the Z2 statistic and Newey-West corrected Fama-MacBeth standard errors do not correct for both cross-sectional and time-series d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
469
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,193 publications
(522 citation statements)
references
References 66 publications
15
469
0
2
Order By: Relevance
“…A 3-month lag period was used to allow time for accounting information to be communicated to the public. Following Chen, Liu and Ryan (2008), Gow, Ormazabal and Taylor (2010) and Peterson (2009), we corrected for cross-sectional and time-series dependence in our data by clustering standard errors by firm and by year. Peterson (2009) argues that clustering standard errors on multiple dimensions (by firm and by year) will yield correct inferences and correct for correlated residuals in the dataset.…”
Section: Methods Value Relevance Of Interim Financial Statementsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 3-month lag period was used to allow time for accounting information to be communicated to the public. Following Chen, Liu and Ryan (2008), Gow, Ormazabal and Taylor (2010) and Peterson (2009), we corrected for cross-sectional and time-series dependence in our data by clustering standard errors by firm and by year. Peterson (2009) argues that clustering standard errors on multiple dimensions (by firm and by year) will yield correct inferences and correct for correlated residuals in the dataset.…”
Section: Methods Value Relevance Of Interim Financial Statementsmentioning
confidence: 99%
“…***, ** and * denote significance at the 1%, 5% and 10% level, respectively. (Gow et al 2010) of Equation 1. The sample consists of a pooled dataset (annual and interim data combined into one dataset) for annual and interim accounting data.…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the relation between the persistence of firm earnings components and matching, we utilize the following OLS regressions that model one-year ahead earnings (cash flows) as a function of industry-wide and firm-specific earnings components. Following Gow et al (2010), we use the two-way clustered standard errors (by firm and year) to report the p-values, controlling for heteroscedasticity and correlation among our firm-year observations.…”
Section: Resultsmentioning
confidence: 99%
“…Petersen (2009) compared these resistive standard errors, and proposed to use two-way clustered resistive standard errors for resistivity control. Gow, Ormazabal and Taylor (2010) found that two-way clustered resistive standard errors are required for a valid deduction in many accounting practices. On the other hand, two-way clustering method can be used for only specific and limited error structures .…”
Section: Methodsmentioning
confidence: 99%